2015
DOI: 10.1016/j.carbon.2015.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Generation of nitrogen functionalities on activated carbons by amidation reactions and Hofmann rearrangement: Chemical and electrochemical characterization

Abstract: Please cite this article as: Mostazo-López, M.J., Ruiz-Rosas, R., Morallón, E., Cazorla-Amorós, D., Generation of nitrogen functionalities on activated carbons by amidation reactions and Hofmann rearrangement: chemical and electrochemical characterization, Carbon (2015), doi: http://dx. AbstractNitrogen functionalization of a highly microporous activated carbon (BET surface area higher than 3000 m 2 /g) has been achieved using the following sequence of treatments: (i) chemical oxidation using concentrated nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 54 publications
7
60
0
Order By: Relevance
“…The changes in surface chemistry on the sample KUA-CONH2 have been previously studied [11], and we found that this increase in oxygen was related to the chemical oxidation treatment carried out prior to amidation step. In case of KUA-N, TPD measurements show a relevant decrease in the CO-evolving groups, with a net total decrease (490 µmol /g) that is especially relevant in the region of thermal decomposition of phenol and quinone-like groups.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…The changes in surface chemistry on the sample KUA-CONH2 have been previously studied [11], and we found that this increase in oxygen was related to the chemical oxidation treatment carried out prior to amidation step. In case of KUA-N, TPD measurements show a relevant decrease in the CO-evolving groups, with a net total decrease (490 µmol /g) that is especially relevant in the region of thermal decomposition of phenol and quinone-like groups.…”
Section: Resultsmentioning
confidence: 57%
“…In our previous work [11], an approach for the incorporation of amides over activated carbon was satisfactorily developed. Also, other nitrogen functional groups were introduced on the surface of the carbon material via secondary reactions.…”
Section: Synthesis Of Kua-conh2mentioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical techniques have been successfully used for the covalent and non-covalent functionalization of different carbon materials with nitrogen functional groups [21], [22] and polymers [23], [24]. The modification of carbon nanotubes using 4-aminobenzoic acid (4-ABA), 4-aminobenzenesulfonic acid (4-ABSA) and 4-aminobenzylphosphonic acid (4-ABPA) in aqueous solution, is an illustrative example of the potential of this method to functionalize with different heteroatoms [8], [25]- [27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%